CONTRIBUTION OF CUMARU AND CASSAVA TO THE ECONOMIC VIABILITY OF AGROFORESTRY SYSTEMS IN THE EASTERN AMAZON - Igo Leite Soares, Francisco; Almeida Vieira, Thiago; Aurélio Oliveira Santos, Marco; Cleiton da Silva Paiva, Francisco; Bizerra da Costa, Marilene; Paiva da Silva, Kennedy (Revista Gênero e Interdisciplinaridade, 2026)
Agroforestry systems (AFS) are composed of arrangements of species that allow for different productive strategies and augment the economy in rural properties and communities, such as in agrarian reform settlements, mainly in the Brazilian Amazon. In the cultivated spaces, it is possible to plan the staggering of production, as the system can consider plant and animal species to provide combinations of food, raw materials, and environmental services. In this work, the economic viability of two species in Agroforestry Systems in the Sustainable Development Project (SDP) Paraíso in Alenquer, in the state of Pará, was evaluated. Data were collected for the period from 2018 to 2021, calculating the following variables: revenues, costs/expenses, profit/loss, payback period, Net Present Value (NPV), Equivalent Annual Value (EAV), and Internal Rate of Return (IRR). All analyses were carried out considering this five-year time frame, showing that the highest profitability of cassava occurs in operations with scale for the production of flour, as well as gains from the sale of tonka bean or cumaru (Dipteryx odorata). The AFS are economically viable with high profitability in most productive arrangements. The low investment, flour sales strategies, and the high demand for tonka beans allow the producers to recoup investments in less than 8 months.